Oferta de alojamientos por medio de la plataforma digital Airbnb en la Provincia de Los Ríos - Vera Zamora, Jorge Luis (2025)
This case study entitled “Offering accommodation through the digital platform Airbnb in the province of Los Ríos” highlights the impact on local tourism, its advantages and disadvantages, such as lack of information and poor marketing strategies. Likewise, the origins of Airbnb are described within the conceptual framework, its collaborative economy model within the province and its presence since 2013, which allows owners to rent spaces temporarily and generate income. The problem is presented as a limited offer of accommodation in the area, and the lack of advertising on the digital platform. The methodology that was proposed in this study is based on a qualitative approach with descriptive and analytical methods, of a documentary nature, to write the findings found through research on the platform, its use and information in general. The results, on the other hand, show a slight increase in the use of Airbnb, the preference of the population for this type of accommodation is due to its ease of obtaining and competitive prices in the hotel sector. In conclusion, it can be deduced that the Airbnb digital platform has diversified the province's tourism offer, benefiting owners and visitors, while facing challenges in competition with hotels and the need for greater promotion, where, ultimately, it is recommended to implement dissemination strategies and present clear standards to strengthen the impact of Airbnb in the local tourism sector.